Pengaruh Non Performing Loan Sebagai Dampak Krisis Keuangan Global terhadap Profitabilitas Perusahaan Perbankan - Sari, Tia Melya; Syam, Dhaniel; Ulum, Ihyaul (Journal of Accounting and Investment, 2012)
The research purpose is to examine the effect of non-performing loans (NPL) in the global financial crisis on the corporate profitability of banks (listed on the Stock Exchange in 2003-2010). Independent variable in this research is Non Performing Loan (NPL) and the dependent variable is probability by return on asset.Sampling technique is used non-probability purposive sampling, so to be concludedÂ  the samples used 15 banks. The method of the research is quantitative and description data non performing loan and probability (return on asset) bank listing on the Stock Exchange 2003-2010 period. Which are then analyzed by employing statistical analysis, such as simple linier regression, correlation analysis, determination coefficient analysis, and t-test. The data is calculated by SPSS 16 for windows. Based on the research result, there is not influence between non performing loan to probability (return on asset). The two variables show a very weak correlation at 0,142 with negative correlation value. This mean if non performing loan is increasing, profitability (return on asset) is decreasing and vice versa. The determination coefficient is 2% and the rest 98% which is influence by other factors. While in the hypothesis examination using t test, t calculation is -1,563 and t table 1,658. As such H0 is accepted. So in conclusion, nonÂ  performing loan does not significantly affect the level of profitability (ROA) company. Because the intermediary function of banks is not running properly.